(untitled) (Contemporary Mathematics, 2021)
With the objective of considering evolution algebras as Banach algebras, we show in this paper new results on normed evolution algebras obtained after the introduction of an evolution algebras operator, which generalizes the one introduced by Tian. The properties of this operator which let evolution algebras be endowed with a Banach space structure are shown.